Evaluation of The National Strategic Project for The Construction of The Serang-Panimbang Expressway - Alifah Azahra Yamin; Laeli Nur Khanifah; Modella Raghel Monika; Inashaqi Salamah (Journal of Human Interaction and Social Studies, 2026)
This study evaluates the implementation of the Serang Panimbang Expressway as a National Strategic Project in Indonesia using William N. Dunn’s policy evaluation framework. The research employed an empirical qualitative approach through a single instrumental case study design. Data were collected through semi structured interviews with key stakeholders involved in project planning, implementation, and supervision, supported by documentary evidence from government reports and policy documents. The analysis focused on six evaluation dimensions consisting of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the project has significantly improved regional connectivity and strengthened development opportunities in previously less accessible areas. Implementation performance was influenced by land acquisition challenges, financial constraints, cost escalation, and administrative coordination issues that affected project timelines. Stakeholders generally perceived the project as strategically beneficial for regional economic growth, although concerns remained regarding the distribution of benefits, environmental impacts, and institutional responsiveness to public complaints. The study concludes that the project remains appropriate and justified within the National Strategic Project agenda because its long term public value exceeds the implementation challenges encountered. Strengthening environmental governance, community engagement, and interinstitutional coordination is essential to improve the sustainability and legitimacy of future infrastructure development initiatives.